Higher serum total bilirubin predicts high risk of 3-year adverse outcomes in patients undergoing primary percutaneous coronary intervention - Gao F; Qiang H; Fan XJ; Xue Q; Bai L (Dove Medical Press, 2019)
Fan Gao,1 Hua Qiang,2 Xiao-Juan Fan,2 Qi Xue,3 Ling Bai21Clinical Research Center, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Department of Cardiovascular Medicine, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China; 3Institut des Sciences de la Terre, Centre National de la Recherche Scientifique, Saint-Martin-d’Hères, FrancePurpose: Previous research findings on the association between serum total bilirubin (TB) and cardiovascular events varied with different study populations. Our objective was to clarify the association between serum TB at admission and long-term adverse outcomes in patients with acute coronary syndrome (ACS) and stable angina (SA) undergoing percutaneous coronary intervention (PCI).Patients and methods: This prospective cohort study included 2,502 patients who underwent PCI. Information on the study population was obtained from the Dryad Digital Repository. The patients were divided into two groups: high (>0.60 mg/dL) and low TB groups (≤0.60 mg/dL) based on the optimal cutoff value achieved in the receiver operating characteristic curve analysis. The relationships between serum TB at admission and clinical outcomes after PCI were analyzed in multivariable logistic regression models and restricted cubic spline.Results: In all patients undergoing PCI, TB>0.60 mg/dL was associated with major adverse cardiovascular events (MACE) and cardiovascular death during a 3-year follow-up. The odds ratio (95% confidence interval) was 1.60 (1.22–2.10) and 1.81 (1.22–2.70) for MACE and cardiovascular death, respectively. The association between TB and MACE was not altered by clinical presentation (p for interaction=0.949).Conclusion: In patients with ACS and SA undergoing PCI, elevated serum TB was associated with increased risk of MACE and cardiovascular death.Keywords: bilirubin, acute coronary syndrome, stable angina, primary percutaneous coronary intervention, major adverse cardiovascular; cerebrovascular events